Effects of soy protein composition in recombined soy‐based cream on the stability and physical properties of whipping cream. (17th February 2020) - Fu, Liwei; He, Zhiyong; Zeng, Maomao; Qin, Fang; Chen, Jie
Abstract: BACKGROUND: Recombinant plant‐based whipping cream (RSWC) has been widely studied in recent years. The present study investigated the effects of soybean protein and its hydrolysates on the stability and physical properties of the RSWC. The RSWC was made with 28% soybean oil bodies and 4% additional soy proteins or its hydrolysates. The proteins used were soy protein isolate, 7S, 11S, oil body protein, soybean proteins isolate hydrolyzed by pepsin (SPHPe) and soybean protein isolate hydrolyzed by papain (SPHPa). RESULTS: RSWC made with SPHPa containing a large amount of small‐molecule polypeptide had the lowest apparent viscosity, shortest whipping time, best overrun and worst whipping stability, whereas RSWC made with SPHPe containing the α, β subunit and small‐molecule polypeptides exhibited the second highest overrun and best whipping stability. The partial coalescence of fat and confocal micrographs of cream emulsions suggested that oil body protein was displaced by the small peptides from the interface, which led to partial destabilization and sufficient coalescence of fat globules after aging and whipping. CONCLUSION: Selectively hydrolyzed soy protein, such as SPHPe, can be used for the production of RSWC with sufficient overrun and whipping stability. This research is of great significance and opens a route to production of the recombinant plant‐based cream in the future. © 2020 Society of Chemical Industry